A quantitative study of Michigan's criminal HIV exposure law. - Galletly, Carol L; Pinkerton, Steven D; Difranceisco, Wayne (AIDS care, 2012)
The objectives of the project were (1) to determine the extent to which HIV-positive persons living in Michigan were aware of and understood Michigan's criminal HIV exposure law, (2) to examine whether awareness of the law was associated with seropositive status disclosure to prospective sex partners, and, (3) to examine whether awareness of the law was associated with potential negative effects of the law on persons living with HIV (PLWH) including heightened HIV-related stigma, perceived societal hostility toward PLWH, and perceived need to conceal one's HIV infection. The study design was cross-sectional. A statewide sample of 384 PLWH in Michigan completed anonymous pen and paper surveys in 1 of 25 data collection sessions. A majority of participants were aware of Michigan's HIV exposure law. Awareness of the law was not associated with increased seropositive status disclosure to all prospective sex partners, decreased HIV transmission risk behavior, or increased perceived responsibility for HIV transmission prevention. However, awareness of the law was significantly associated with disclosure to a greater proportion of sex partners prior to respondents' first sexual interaction with that partner. Awareness of the law was not associated with increased HIV-related stigma, perceived societal hostility toward PLWH, or decreased comfort with seropositive status disclosure. Evidence of an effect of Michigan's HIV exposure law on seropositive status disclosure was mixed. Further research is needed to examine the various forms of HIV exposure laws among diverse groups of persons living with or at increased risk of acquiring HIV.
Keywords: Adult; Aged; Criminal Law; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; HIV Infections; HIV Seropositivity; Humans; Male; Michigan; Middle Aged; Self Disclosure; Sexual Behavior; Sexual Partners; Social Stigma; Young Adult